Penerapan D & M IS Succsess Model Terhadap Aplikasi SIMPEL (Sistem Informasi Pemantauan Tindak Lanjut) - Yogi Primadasa; Rakhmad Kuswandhie; Ihsan Verdian; Afdhal Shafnur (CogITo Smart Journal, 2023)
The D&M IS Success Model is an information system success testing model that is viewed based on 6 dimensions, namely system quality, information, use, satisfaction, and the last is the impact caused by both individual users and organizations. The quality of a system and information has an important relationship in terms of influencing whether or not the information system is used and also affects user satisfaction in communicating the system, both of which will have a positive or negative impact on the user experience individually and the organization as a whole. The SIMPEL application is an information system developed and implemented since 2020 by the Lubuklinggau City Inspectorate. Since the application of this application has not been evaluated for improvement, this is what made this research carried out, namely to test the success of SIMPEL implementation using the D&M IS Success Model. The results of the data processing are in the form of the average value of the correspondent answers based on the indicators for each variable presented by the D&M Success Model